2020
DOI: 10.1287/trsc.2020.0996
|View full text |Cite
|
Sign up to set email alerts
|

The Stochastic Multipath Traveling Salesman Problem with Dependent Random Travel Costs

Abstract: The objective of the stochastic multipath traveling salesman problem is to determine the expected minimum-cost Hamiltonian tour in a network characterized by the presence of different paths between each pair of nodes, given that a random travel cost with an unknown probability distribution is associated with each of these paths. Previous works have proved that this problem can be deterministically approximated when the path travel costs are independent and identically distributed. Such an approximation has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…For a detailed and exhaustive presentation of the various theoretical steps that lead to the above results, the reader is referred to Perboli et al (2014), Tadei et al (2009), andFadda et al (2020). For the sake of completeness, it is interesting to remark that, in the case of a maximization problem, the same formula in (9) holds with some minor changes regarding the computation of e q i , i.e.,…”
Section: The Evtda For Mssp DC Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a detailed and exhaustive presentation of the various theoretical steps that lead to the above results, the reader is referred to Perboli et al (2014), Tadei et al (2009), andFadda et al (2020). For the sake of completeness, it is interesting to remark that, in the case of a maximization problem, the same formula in (9) holds with some minor changes regarding the computation of e q i , i.e.,…”
Section: The Evtda For Mssp DC Problemsmentioning
confidence: 99%
“…Therefore, this assumption is a very mild assumption on the distribution of the random oscillations, and thus it does not significantly preclude the deployment of the EVTDA for practical applications. It is important to remark that Assumption 3, in the general form presented above, has been derived only recently in Fadda et al (2020). Therefore, in some other previous papers, the reader could find a more restrictive assumption on the distribution of the oscillations.…”
Section: Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to notice that the assumption needed to apply the proposed EVTDA approach are quite mild and, in any case, less restrictive of those required by the SP paradigm. Interesting enough, Fadda et al (2020) have recently proved that the EVTDA can still be deployed when assumption ( 18) is relaxed to the following condition:…”
Section: Estimation Of the Expected Completion Timesmentioning
confidence: 99%
“…Thus, this is a very mild assumption and, therefore, does not significantly restrict the deployment of the EVTDA approach. It is essential to notice that some empirical results presented in Tadei et al (2017), Fadda et al (2020), and Roohnavazfar et al (2019) have demonstrated the effectiveness of the EVTDA framework even when the distribution of random oscillations does not satisfy the assumption ( 22) like the Uniform distribution.…”
Section: Estimation Of the Expected Completion Timesmentioning
confidence: 99%